THE INFLUENCE OF CORPORATE SOCIAL RESPONSIBILITY CERTIFICATION ON CONSUMER ACCEPTANCE IN THE NETHERLANDS MARKET: A COMPARATIVE STUDY OF COMPANIES FROM INDONESIA AND THE NETHERLANDS - Rahmady Indratno, Haidar (PEOPLE: International Journal of Social Sciences, 2024)
This study explores the relationship between Corporate Social Responsibility (CSR) certification, product country of origin, and consumer acceptance in the Netherlands market, focusing on coffee beans. Rooted in Sen & Bhattacharya (2001) and Matten & Moon’s (2008) insights, the research considers the moderating effect of the country of origin, drawing on Peterson & Jolibert’s (1995) perspectives. By using a randomized detailed survey and a controlled experiment from 200 participants, the study examines the Netherlands market consumer perceptions of companies with high levels of CSR certification from a developed country, the Netherlands, and a developing country, Indonesia. Results confirm a positive correlation between a high level of CSR certification and consumer acceptance in the Netherlands. The influence of the Netherlands as the product’s origin positively moderates this relationship. Surprisingly, products from Indonesia also show a positive impact, contrary to expectations. The findings stress the strategic role of CSR certification for firms in the Netherlands market, irrespective of origin. However, caution is advised due to limitations, including potential bias and a small sample size. In conclusion, this research contributes nuanced insights for businesses navigating global markets, emphasizing the need for a comprehensive understanding of CSR’s impact on consumer acceptance.